A physical model for [C ii] line emission from galaxies. Issue 1 (25th July 2019) - Ferrara, A; Vallini, L; Pallottini, A; Gallerani, S; Carniani, S; Kohandel, M; Decataldo, D; Behrens, C
ABSTRACT: A tight relation between the [C ii ] 158 μ m line luminosity and star formation rate is measured in local galaxies. At high redshift ( z > 5), though, a much larger scatter is observed, with a considerable (15–20 per cent) fraction of the outliers being [C ii ]-deficient. Moreover, the [C ii ] surface brightness (Σ_[C II] ) of these sources is systematically lower than expected from the local relation. To clarify the origin of such [C ii ]-deficiency, we have developed an analytical model that fits local [C ii ] data and has been validated against radiative transfer simulations performed with cloudy . The model predicts an overall increase of Σ_[C II] with ΣSFR . However, for ΣSFR 1 M_yr^-1 kpc^-2, Σ_[C II] saturates. We conclude that underluminous [C ii ] systems can result from a combination of three factors: (a) large upward deviations from the Kennicutt–Schmidt relation (κs ≫ 1), parametrized by the 'burstiness' parameter κs ; (b) low metallicity; (c) low gas density, at least for the most extreme sources (e.g. CR7). Observations of [C ii ] emission alone cannot break the degeneracy among the above three parameters; this requires additional information coming from other emission lines (e.g. [O iii ]88 μ m, C iii ]1909 Å, CO lines). Simple formulae are given to interpret available data for low- and high- z galaxies.